2001
DOI: 10.1007/s004280000378
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelioma-like carcinoma of the urinary bladder: a clinicopathologic study of 13 cases

Abstract: Lymphoepithelioma-like carcinoma (LELCA) of the urinary bladder is a rare variant of bladder cancer characterized by a malignant epithelial component densely infiltrated by lymphoid cells. It is characterized by indistinct cytoplasmic borders and a syncytial growth pattern. These neoplasms deserve recognition and attention, chiefly because they may be responsive to chemotherapy. We report on the clinicopathologic features of 13 cases of LELCA recorded since 1981. The chief complaint in all 13 patients was hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
149
2
22

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(174 citation statements)
references
References 13 publications
1
149
2
22
Order By: Relevance
“…The largest study was reported by Tamas et al8 who described 17 pure 13 mixed LELC. Prior to that Lopez-Beltran et al5 reported 3 pure, 6 predominant and 4 focal LELCs of the urinary bladder. Amin et al3 reported 3 pure, 5 predominant and 3 focal LELCs and Holmang et al6 described 3 pure, 5 predominant and 3 focal cases of LELC.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The largest study was reported by Tamas et al8 who described 17 pure 13 mixed LELC. Prior to that Lopez-Beltran et al5 reported 3 pure, 6 predominant and 4 focal LELCs of the urinary bladder. Amin et al3 reported 3 pure, 5 predominant and 3 focal LELCs and Holmang et al6 described 3 pure, 5 predominant and 3 focal cases of LELC.…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that abnormalities of p53 regulation might be crucial in the pathogenesis of LELC of the urinary bladder 10. Though the exact origin of these carcinomas is not well known, the expression of common urothelial markers suggest that they are probably modified urothelial cells that have derived from stem cells 56…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations